Nature beyond solitude : notes from the field - Farnsworth, John Seibert (Comstock Publishing Associates, an imprint of Cornell University Press, 2020)
"While nature mysticism has always embraced solitude, Farnsworth investigates long-term ecological projects where the experience of community transcends solitary sojourns into the depths of natural history"--